Understanding Nonoffending Caregiver Protection in Child Sexual Abuse - Sally, Christina Lynn (2019)
Child sexual abuse is a global issue that has affected children, families, and communities for centuries regardless of socioeconomic, religious, ethnic, race, or multicultural factors and distinctions. Sexually abused children may be reluctant to disclose sexual abuse due to perceptions or realities that their nonoffending caregiver (NOC) will not believe their reports and may fail to provide adequate protection. The purpose of this quantitative study was to assess if child demographics (i.e., age, sex, and race/ethnicity); type of sexual offense (i.e., contact or noncontact); and perpetrator relationship to the child (i.e., familial or extrafamilial) predict a NOC's response (i.e., protection or failure to protect) to child sex abuse disclosures, using cognitive dissonance theory and neutralization theory as theoretical foundations. Archived and extracted data (2015-2017) were utilized from the Utah Department of Human Services. A binary logistic regression was used to determine the predictive quality of the independent variables for the outcome variable. The results indicated that the odds of protection were greater for non-White females experiencing noncontact abuse by a familial offender. Age was not a statistically significant predictor of NOC protection in the full model. The findings from this study support positive social change by providing research-based conclusions that can promote prevention, intervention, and education programs by child protection teams for victims of child sexual abuse and their families